Die gewöhnliche Gebrauchskeramik vom Magdalensberg - Schindler Kaudelka, Eleny (Verlag des Landesmuseums für Kärnten, 1989)
Excavations on the Magdalensberg in Carinthia, Southern Austria brought to light a huge amount of common wares that have to be divided for study. No parameters to be followed have as yet been fixed and therefore in a first chapter definitions are given on what type of material is used in the book. Red or buff fired liquid containers, mostly wheel turned in Italian workshops out of pretreated clays are dealt with. The chapter chronology approaches the problem form the 40 well defined contexts on different spots of the site, which in 100 years of life offers a division into 7 phases, to be regrouped in 3 periods between 50 BC and 50 AD. A discussion on the possibilities and limits of dating common or utilitarian pottery is included. Typological analysis distinguishes 5 groups, the main one being the Italic shapes and their Hellenistic predecessors. Next come the small transport containers, basically two handled jugs followed by the forms of Celtic inspiration, while a separate chapter combines the single and rare shapes. Some 25 pages are dedicated to the study of results and point out the rare stamps, inscriptions and marks. The plates show drawings and photographs in a typological catalogue as well as a chronological synoptic. A 2012 paper is intended to integrate the Magdalensberg jugs and pitchers into she state of the art. SCHINDLER-KAUDELKA, E., Céramiques communes du Magdalensberg. Un cas exceptionnel dans le Norique. - C. BATIGNE VALLET, Les céramiques communes dans leur contexte régional. Faciès de consommation et mode d'approvisionnement (Lyon 2012), 185-218.